Risk Factor Analysis of Ski and Snowboard Injuries During the 2023/2024 Winter Season: A Single, High-Volume Trauma Center Database Analysis - Michele Paolo Festini Capello; Pieralberto Valpiana; Giuseppe Aloisi; Giovanni Cristofolini; Svea Caren Misselwitz; Giuseppe Petralia; Mario Muselli; Salvatore Gioitta Iachino; Christian Schaller; Pier Francesco Indelli (Medicina)
Background and Objectives: The objective of the study was to evaluate the epidemiology of slope-related accidents in a high-volume trauma center during the winter season. In addition, this study aims to analyze patient-related, equipment-related, and environment-related characteristics. Materials and Methods: A questionnaire containing 22 items was distributed to all adult patients admitted to the emergency department of the Brixen Hospital (Italy) during the 2023/24 winter season because of a ski/snowboard-related injury. Results: The final database included 579 questionnaires from 579 patients who ultimately entered the study: 285 were females and 294 were males. The analysis of risk factors for fractures revealed that patients with fractures were generally older (50.7 ± 16.0 years) compared to those without fractures (45.4 ± 17.2 years, p = 0.0021). Thirty-six percent of injuries were considered as joint sprain/ligament strain: patients in this group were younger (45.5 ± 16.2 years) compared to all patients (48.3 ± 17.3 years, p = 0.0151). Conclusions: In conclusion, this study identified significant risk factors associated with skiing and snowboarding injuries. Fractures were more common among older and more experienced skiers, particularly those who described themselves as experts. Ligamentous distortions were more common among younger and less experienced skiers. Fatigue is generally underestimated, and the general physical preparation is often lacking for sports like skiing and snowboarding. Additionally, the absence of significant correlations between weather conditions, snow quality, equipment type, and the difficulty of the slope with injury risk suggests that individual factors such as age and skill level are more critical determinants of injury risk than environmental or equipment-related factors.